Perancangan Conveyor untuk Memindahkan C Purlin - Dendi Fani Zulfikar; Mohammad Hakam; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Companies engaged in the fabrication sector need a conveyor to move the c purlin from the forming machine to the packaging process. Seeing from these problems, a conveyor design will be carried out. The calculation of machine elements will be carried out to determine the performance of the conveyor and in order to get a good conveyor design. This conveyor has a capacity of 27 tons / day and is large from the rotation of the belt itself, which is 72 rpm. With a speed of 0.38 m/s this conveyor requires an electric motor or ac motor of 0.34 kw or 0.46 hp. This conveyor uses a PVC conveyor belt made of polyester material with a width of 200 mm, a thickness of 3 mm, and there are 2 layers. The total length of this conveyor belt is 17 m. The total weight of this conveyor belt is 44.88 kg and the weight per meter is 2.64 kg. There are four stress points that occur on the conveyor belt, namely 58.64 kg, 89.79 kg, 96.075 kg, 119 kg. The effective stress on the belt is 62.17 kg. Torque is 2248.45 Nm and has a minimum diameter of 9 mm. On this conveyor using bearings UCFL 204/H. The axial force on the bearing is 524.8 N and the radial force is 299.8 N. The transmission system on the conveyor uses a gearbox with a ratio of 1:20.